Airway wall thickness in patients with near fatal asthma and control groups: assessment with high resolution computed tomographic scanning. Issue 4 (1st April 1998) - Awadh, Nasser; Müller, Nestor L; Park, Chan S; Abboud, Raja T; FitzGerald, J Mark
Abstract : BACKGROUND: Airway wall thickening has been observed in post mortem studies of patients with asthma. Assessment of airway wall thickening by high resolution computed tomographic (HRCT) scanning has been reported in experimental studies. We have used HRCT scanning to measure airway wall thickness at the segmental and subsegmental levels in 40 patients with asthma and 14 normal controls. METHODS: The subjects were prospectively divided into four age and sex matched groups: 14 patients with a history of near fatal attack of asthma (NFA; group 1), 12 patients with moderate asthma (group 2), 13 patients with mild asthma (group 3), and 14 normal controls (group 4). All subjects were non-smokers. High resolution (1 mm collimation) CT scans of the chest were done at five different levels. RESULTS: The mean (SD) forced expiratory volume in one second (FEV1 ) was 68 (20)% of predicted for group 1, 73 (12)% for group 2, 102 (12)% for group 3, and 103 (12)% for group 4. The ratio of airway wall thickness to outer diameter (T/D) and the percentage wall area (WA%) defined as (wall area/total airway area) × 100 were used to compare airway wall thickness between the groups. The mean (SD) T/D and WA% were 0.27 (0.05) and 78.0 (9.2)% for group 1, 0.27 (0.05) and 78.8 (9.2)% for group 2, 0.25 (0.04) and 74.2 (7.5)% for group 3, and 0.23 (0.04) and 70.9 (8.2)% for group 4. T/D and WA% were not significantly different between groups 1 and 2. However, both groups 1 and 2 had higher T/D and WA% than either group 3 or 4 (p < 0.001) and group 3 had a higher T/D and WA% than group 4 (p < 0.03).The differences (95% CI) between the groups in WA% were 7.1% (0 to 14.4) for groups 1 and 4, 3.8% (–3.4 to 10) for groups 1 and 3, and 3.3% (–4.4 to 10) for groups 3 and 4. The differences between the groups in T/D and WA% were noted both for those with airways with a luminal diameter of >2 mm and those with a luminal diameter of ⩽2 mm. CONCLUSIONS: All the patient groups had greater airway wall thickening than the normal subjects as assessed by HRCT scanning, but patients with more severe asthma had greater airway wall thickening than those with mild asthma. The methodology described in this study may be useful in assessing airway calibre in early intervention studies with anti-inflammatory therapy.